Pengaruh Keselamatan Kerja, Kesehatan Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan (Studi pada Karyawan Perusahaan Pengolahan Hasil Kelautan Di Kabupaten Rembang) - Kamawati, Legita Agustina; Sari, Dian Anita (Universitas Batanghari, 2024)
Employee performance is the overall result of carrying out their duties and roles within a specific period of time in achieving organisational or company goals. Good employee performance will create significant business growth and low performance will also adversely affect the continuity of the company. Employee performance can be seen in terms of quality, quantity and work time in achieving company goals. The purpose of this study was to show and explain the effect of safety, health and work environment on employee performance of marine product processing companies in Rembang Regency. This study used accidental sampling technique to get a sample of 73 respondents. The data source in this research is primary data by distributing questionnaires to employees. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that occupational safety, occupational health and work environment partially have a significant positive effect on employee performance.